A high proportion of Vibrio cholerae strains isolated from children with diarrhoea in Bangkok, Thailand are multiple antibiotic resistant and belong to heterogenous non-O1, non-O139 O-serotypes. - Dalsgaard, A. (Cambridge University Press, 1999)
Results of a surveillance on cholera conducted with patients seen at the Children Hospital in Bangkok, Thailand from August 1993 to July 1995 are presented. Annually, isolation rates for Vibrio cholerae varied between 1.7 and 4.4% of patients with diarrhoea. V. cholerae O1 serotype Ogawa accounted for between 31 and 47% of patients cultured positive for V. cholerae, whereas the O139 serotype dominated in early 1994 after which it disappeared. Non-O1, non-0139 strains were isolated at similar rates as serotype O1 in 1993 and 1994, but accounted for 69% of V. cholerae culture positive specimens in 1995. However, the annual proportion of the isolation of non-O1, non-O139 strains showed little variation and remained low between 1.0 and 1.3%. Serotyping of 69 epidemiological unrelated non-O1, non-O139 strains produced 37 different O-serotypes. BglI ribotyping of serotypes containing more than two strains demonstrated a high degree of heterogeneity within and between serotypes, except seven serotype O37 strains which showed an identical ribotype suggesting clonality. None of the 69 strains hybridized with a cholera toxin probe and only two strains hybridized with a heat-stable enterotoxin probe. Susceptibility testing to 12 antibiotics showed that 40 of 69 (58%) non-O1, non-O139 strains were resistant to colistin, streptomycin and sulphisoxazole and 28 of 69 (41%) were multiple antibiotic resistant (MAR; > or = 4 antibiotics). Although 26 of 69 (38%) strains contained one or more plasmids, the plasmids were of low molecular weights and did not seem to encode antibiotic resistance. The results of the present study showed that a high proportion of heterogenous MAR V. cholerae non-O1, non-O139 strains were isolated from children at the hospital. With reference to the emergence of V. cholerae O139 in 1992, we suggest that non-O1, non-O139 strains should be monitored carefully to detect new serotypes with a possible epidemic potential, but also to determine the development and mechanism of antibiotic resistance.